2012
DOI: 10.1142/s2010194512005533
|View full text |Cite
|
Sign up to set email alerts
|

Solving Local Minima Problem in Back Propagation Algorithm Using Adaptive Gain, Adaptive Momentum and Adaptive Learning Rate on Classification Problems

Abstract: This paper presents a new method to improve back propagation algorithm from getting stuck with local minima problem and slow convergence speeds which caused by neuron saturation in the hidden layer. In this proposed algorithm, each training pattern has its own activation functions of neurons in the hidden layer that are adjusted by the adaptation of gain parameters together with adaptive momentum and learning rate value during the learning process. The efficiency of the proposed algorithm is compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The author proposed a technique that adjusted the weights by the adaptation of gain parameters together with adaptive momentum and learning rate value during the learning process. The experiments results as presented in [16] demonstrated that the proposed method improved significantly the performance of the learning process.…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…The author proposed a technique that adjusted the weights by the adaptation of gain parameters together with adaptive momentum and learning rate value during the learning process. The experiments results as presented in [16] demonstrated that the proposed method improved significantly the performance of the learning process.…”
Section: Methodsmentioning
confidence: 80%
“…On the other hand, if the learning rate is set to too small, the algorithm will take a long time to converge [12]. Many researches [13,14,15,16] used different strategies to speed up the convergence time by varying the learning rate. The best strategies in gradient descent BP is that it utilizes larger learning rate when the neural network model is far from the solution and smaller learning rate when the neural net is near the solution [17].…”
Section: Methodsmentioning
confidence: 99%
“…However, BPNN has two major limitations, being the low convergence rate and the instability [33]. These limitations are the results of being trapped in a local minimum [34], [35] and the possibility in overshooting the minimum of the error surface [33].…”
Section: Related Workmentioning
confidence: 99%
“…In the next step, besides the MSE, the network information back propagates from the output layer to the input layer, and specific connector weights are updated utilizing a "generalized ∆ rule" that is held of learning rate (η) and momentum constant (α) [11]. Equations 3 and 4 display the rule of weight updating.…”
Section: A Back-propagation Algorithmmentioning
confidence: 99%
“…For achieving the average η which gives the least MSE, rigorous parametric research has been conducted in this research [11]. The η at which the error is minimal is determined for the association with the SA algorithm.…”
Section: A Back-propagation Algorithmmentioning
confidence: 99%